A SYSTEMATIC REVIEW POSISI INTUBASI YANG BAIK PADA PASIEN OBESITAS - Arifah, Maulina; Gofur, Abdul (Jurnal Nusantara Mandani, 2023)
ABSTRACT Background: Obesity is such a growing problem globally that an anesthesiologists must be good at regulating the management of their airway difficulties, in this review it is discussed whether the position of ramped laryngoscopy or sniffing is better for tracheal intubation which is still unclear. Objective: This review aims to determine the efficacy of tracheal intubation in the ramped or head up position and the supine or sniffing position mainly in patients who have indications of intubation difficulties in obese patients. Methods: The authors conducted a systematic review and meta-analysis of randomized clinical trials to compare the ramped position with the sniffing position for tracheal intubation. We searched the Pubmed, Science Direct, Google Scholar, and the World Health Organization Clinical Trial Registration Platform until June 2022. The authors also conducted searches through citations by including randomized controlled trials, trials of participants requiring tracheal intubation in any setting, and those that compared tracheal intubation in ramped and sniffing positions, head up, and supine. Conclusion : This systematic review, which includes all available RCTs at two intubation positions, shows there are significantly beneficial benefits of a ramp position or head up position rather than a sniffing position or supine position. Thus, more research is needed to identify the advantages of one of these positions for trachea intubation especially in individuals with obesity as well as indications of intubation difficulties. Keywords : Obesity; Position; Intubation Abstrak Latar belakang: Latar Belakang: Obesitas merupakan masalah yang berkembang secara global sehingga seorang ahli anestesi harus pandai mengatur tatalaksana kesulitan jalan nafasnya, dalam review ini dibahas apakah posisi ramped laryngoscopy atau sniffing lebih baik untuk intubasi trakea yang masih belum jelas. Tujuan: Review ini bertujuan untuk mengetahui efikasi intubasi trakea pada posisi ramped atau head up dan posisi supine atau sniffing terutama pada pasien yang memiliki indikasi kesulitan intubasi pada pasien obesitas. Metode: Penulis melakukan kajian sistematis dan meta-analisis uji klinis acak untuk membandingkan posisi ramped dengan posisi sniffing untuk intubasi trakea. Kami menelusuri database Pubmed, Science Direct, Google Scholar, dan Platform Pendaftaran Uji Klinis Organisasi Kesehatan Dunia hingga Juni 2022. Para penulis juga melakukan pencarian melalui kutipan dengan memasukkan uji coba terkontrol secara acak, uji coba peserta yang membutuhkan intubasi trakea dalam pengaturan apa pun, dan yang membandingkan intubasi trakea dalam posisi menggenjot dan mengendus, kepala tegak, dan terlentang. Kesimpulan : Tinjauan sistematis ini, yang mencakup semua RCT yang tersedia pada dua posisi intubasi, menunjukkan bahwa ada keuntungan yang signifikan dari posisi ramp atau posisi head up daripada posisi mengendus atau posisi terlentang. Dengan demikian, penelitian lebih lanjut diperlukan untuk mengidentifikasi keuntungan dari salah satu posisi intubasi trakea ini terutama pada individu dengan obesitas serta indikasi kesulitan intubasi. Kata Kunci : Obesitas, Posisi, Intubasi